'Bless you'- a case of oropharyngeal perforation secondary to sternutation - Ben Walters; Amy Lovett; Ding Yang; Elizabeth Ross (Otolaryngology Case Reports, 2022)
Spontaneous perforation of the pharynx has been rarely reported in the literature. Cases of barotrauma from stifling a sneeze have been reported previously. Symptoms are often non-specific which makes diagnosis challenging. We report a case of 63-year-old man nearing completion of chemoradiotherapy for base of tongue squamous cell carcinoma who was referred after feeling a ‘tearing’ sensation in his neck after sneezing. This is the first case reported in the literature of oropharyngeal perforation secondary to a sneeze in a patient with a head and neck tumour undergoing radiotherapy.